Use of a counsellor supported disclosure model to improve the uptake of couple HIV testing and counselling in Kenya: a quasi-experimental study - Margaret Kababu; Eric Sakwa; Robinson Karuga; Annrita Ikahu; Inviolata Njeri; Jordan Kyongo; Catherine Khamali; Wanjiru Mukoma (BMC, 2018)
Abstract Background Heterosexual couples account for 44% of new HIV infections in Kenya and there's low awareness of self and partner HIV status. Different strategies have been employed to promote couple HIV testing and counselling (CHTC). Despite this, HIV incidence among couples continues to rise. This study sought to assess the use of a counsellor-supported disclosure (CSD) model in enhancing the uptake of CHTC and the factors that were associated with it. Methods A pre-post quasi experimental study design with an intervention and a comparison arm was utilized. The study was conducted in Nairobi, Nakuru, Kisumu, and Homa Bay counties in Kenya. A total of 276 participants were recruited; 149 and 127 in the comparison and intervention arms, respectively. Standard HIV testing & counselling (HTC) was offered in the comparison arm whereas the counsellor-supported disclosure model was administered in the intervention arm. The model empowered index clients to invite their sexual partner for CHTC. Telephone follow-up and subsequent community health volunteer (CHV) follow-up for non-responders were embedded in the model. Semi-structured questionnaires were used to collect data at baseline and 3 months into the study. In-depth interviews were conducted with 15 participants who took up the intervention and 7 of the HTC providers who offered CSD. The quantitative and qualitative data were analyzed using STATA version 13 and NVIVO 10, respectively. Results Uptake of CHTC was 28% in the intervention arm of the study compared to 7% in the comparison arm (p < 0.001). Participants in the intervention arm of the study had eight times higher odds of taking up CHTC compared to their counterparts. The outcome of the qualitative interviews revealed that the CSD counselling, skills on partner invitation, and follow-up for partner invitation increased the uptake of CHTC. On the other hand, unwillingness to test together with partner, lack of availability to test together as a couple, and provision of the wrong contact information by the participants reduced the uptake of CHTC. Conclusion The CSD model improved the uptake of CHTC. This model can be integrated into the existing HTC structures to enhance the uptake of CHTC.